Reduction of environmental impact in mines with the disposition of residual in underground in the Casablanca mine - Toledo Garay, Fernando Enrique (2006)
To significantly minimize the environmental impact taken place by the system of having underground mined, it has to arrange the solid residuals and the tailing inside of the mines, occupying the open cavities originated by the exploitation of the ore. This hypothesis demonstrated, the viability of minimizing the environmental impact generate for the mining industry, based on the theoretical mark of the quality mining exploitation. This research demonstrates that if the economic ore is extracted, but the bargain and but the strictly necessary of rock to give access to the machinery, we’ll be able to have inside mines 86% to 88% tailing in new mines, and 100% in old mines as Casapalca mine, with derisive investment of U.S.$ 6 109 000.00, but being achieved great profitability with a Net Present Value (NPV) of U.S.$ 28 400 000.00, and with Internal Rate of Return (IRR) of 465%. In underground mining, the dilution increment is an indicator of the drop quality of techniques applied in the mines exploitation that it translates himself in fall productiveness; where human and physiques resources are used to extract waste that contaminate the environment. This research intends to radically change the systems and methods used to mine, preparing stops with bridges and pillars replaced previously with strengthen concrete or cemented tailing, in order to recover the contained ore totally. In this manner, it will be able to guarantee the total retention of fluid tailing, to cry up, the water to filter and to check the drainage to circulate very close to the extracting the circuit with concentration plant, after of mass all ore contents in each stop. The obtain advantages with this new system, to goodwill of the managers, the benefit of social turn and the environmental preservation, they are: First, the recovery of 10% to 15% ore inventory. Second, to avoid that collapse the mine to outburst of the hanging and foot wall rock ( very ordinary at the Casapalca mine), With consequently loss of money in equipment to ove taker, ore to inter and until loss life humans. Third, they’ll have parsimony in support or mine and environmental reparation. I acquaint that it isn’t discuss of to arrange the tailing like hydraulic fill, only applied to the Cut and Fill methods, technique that only partially has solved the problem of tailing disposition, not the impact taken place by the increment of the fine ones in the tailing dam.